The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1111/his.12625
|View full text |Cite
|
Sign up to set email alerts
|

GATA‐binding protein 3, gross cystic disease fluid protein‐15 and mammaglobin have distinct prognostic implications in different invasive breast carcinoma subgroups

Abstract: The commonly used breast carcinoma biomarkers vary in their prognostic implications. GCDFP-15 independently indicated a favourable prognosis, especially in ER-negative, HER2-positive and molecular apocrine cancers. GATA-3 and MGB were not associated with outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…Expression of GATA3, GCDFP15 and MGB has been reported in 32-100%, 23-78% and 48-73% of IBCs, respectively. [1][2][3][4][5][6][7][8][9][10][11][12] These markers showed high expression in hormonal receptor (HR)-positive and human epidermal growth factor receptor 2 (HER2)positive cancers, but low expression in triple-negative breast cancers (TNBCs). 1,4,6,12,13 Some studies reported GATA3 expression in >90% of HR-positive cancers, whereas only 20-66% of TNBCs showed expression when a certain clone of GATA3 (L50-823) was used.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of GATA3, GCDFP15 and MGB has been reported in 32-100%, 23-78% and 48-73% of IBCs, respectively. [1][2][3][4][5][6][7][8][9][10][11][12] These markers showed high expression in hormonal receptor (HR)-positive and human epidermal growth factor receptor 2 (HER2)positive cancers, but low expression in triple-negative breast cancers (TNBCs). 1,4,6,12,13 Some studies reported GATA3 expression in >90% of HR-positive cancers, whereas only 20-66% of TNBCs showed expression when a certain clone of GATA3 (L50-823) was used.…”
Section: Introductionmentioning
confidence: 99%
“…GATA3 has been studied extensively in a number of tumour types, including breast and urothelial carcinomas for use as an adjunct to diagnosis . However, although GATA3 has long been associated with ER expression in luminal breast carcinomas and is used frequently to support the origin of metastatic tumours, there has been an increasing number of publications documenting both protein and gene expression in triple‐negative breast cancers (TNBC) . Indeed, Hou et al .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] However, although GATA3 has long been associated with ER expression in luminal breast carcinomas and is used frequently to support the origin of metastatic tumours, 15,[17][18][19][20][21] there has been an increasing number of publications documenting both protein and gene expression in triple-negative breast cancers (TNBC). 15,[20][21][22][23][24] Indeed, Hou et al 25 recently reported more than 23% of primary and 26% of metastatic TNBCs to be GATA3-positive using immunohistochemisty.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of GATA3 expression has been associated with unfavorable clinical outcome and worse survival [15,[23][24]. However, no association with outcome has been observed in other studies [25]. In one study, GATA3 expression was found to be associated with favorable outcome in all the breast tumors in the study, while the association was lost when only ER positive cancers were analyzed [26].…”
Section: Discussionmentioning
confidence: 90%